2004
DOI: 10.1093/pasj/56.1.207
|View full text |Cite
|
Sign up to set email alerts
|

Three-Dimensional Magnetohydrodynamic Numerical Simulations of Coronal Loop Oscillations Associated with Flares

Abstract: We performed three-dimensional MHD numerical simulations for solar coronal magnetic loop oscillations and found: (1) The loop oscillation period is determined by its Alfvén time. (2) The amplitude of oscillation decreases exponentially in time. This is explained as energy transport by fast-mode MHD waves. The damping rate, $\omega _\mathrm{damp}$, is described as $\omega _\mathrm{damp} \propto V_\mathrm{a}/R$, where $V_\mathrm{a}$ is the Alfvén speed around loops and $R$ is the radius of the loop. Because of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(30 citation statements)
references
References 18 publications
1
29
0
Order By: Relevance
“…These authors considered a dipole magnetic field rather than the arcade studied here; however, it shares the property of being a symmetric but non-uniform field, so Alfvén waves may be supported by the flux surfaces defined by the field. Miyagoshi et al (2004) excited oscillations by applying a velocity field to the top of their loop in a way similar to our internal driver. For our internal excitation simulations, we find the period of oscillation is consistent with P k , whereas Miyagoshi et al (2004) described the period of oscillation in terms of the Alfvén speed at the loop top and found that P ∝ ρ 0.33 0 .…”
Section: Simulation With No Loop Structurementioning
confidence: 99%
See 2 more Smart Citations
“…These authors considered a dipole magnetic field rather than the arcade studied here; however, it shares the property of being a symmetric but non-uniform field, so Alfvén waves may be supported by the flux surfaces defined by the field. Miyagoshi et al (2004) excited oscillations by applying a velocity field to the top of their loop in a way similar to our internal driver. For our internal excitation simulations, we find the period of oscillation is consistent with P k , whereas Miyagoshi et al (2004) described the period of oscillation in terms of the Alfvén speed at the loop top and found that P ∝ ρ 0.33 0 .…”
Section: Simulation With No Loop Structurementioning
confidence: 99%
“…Miyagoshi et al (2004) excited oscillations by applying a velocity field to the top of their loop in a way similar to our internal driver. For our internal excitation simulations, we find the period of oscillation is consistent with P k , whereas Miyagoshi et al (2004) described the period of oscillation in terms of the Alfvén speed at the loop top and found that P ∝ ρ 0.33 0 . Figure 10 shows the dependence on the period of oscillation on the density contrast.…”
Section: Simulation With No Loop Structurementioning
confidence: 99%
See 1 more Smart Citation
“…More realistic, bipolar magnetic field (e.g. Miyagoshi et al 2004;McLaughlin & Ofman 2008;Selwa & Ofman 2009;Selwa et al 2011aSelwa et al ,b, 2013Pascoe & De Moortel 2014) or extrapolated magnetogram based magnetic field (e.g., Ofman 2007;Schmidt & Ofman 2010) and gravitationally stratified density structures were modeled with 3D MHD in order to study waves, clearly demonstrating the advantage of considering 3D realistic magnetic field topology on unambiguous determination of seismologically derived coronal magnetic field.…”
Section: Introductionmentioning
confidence: 99%
“…Other works have also included the curvature of a loop in either 1D or 2D geometry, and even non-planar loops (Ruderman & Scott 2011). Rigorous 3D MHD simulations have also been performed (e.g., Miyagoshi et al 2004;Ofman 2009;Selwa & Ofman 2010).…”
Section: Introductionmentioning
confidence: 99%